2022
DOI: 10.1039/d2nr04231b
|View full text |Cite
|
Sign up to set email alerts
|

Type-I PtS2/MoS2 van der Waals heterojunctions with tunable photovoltaic effects and high photosensitivity

Abstract: Recent advance in two-dimensional (2D) materials is an essential factor to boosting modern electronics and optoelectronics. So far, transition metal dichalcogenides (TMDs) as an emerging member of 2D materials, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
11
0
1
Order By: Relevance
“…When α = 0, the photocurrent is determined by the photogating effect involving the trapping state; when α = 1, the photocurrent is determined by the photoconductive effect. [ 32,33 ] The extracted α is between 0 and 1, indicating the coexistence of these two mechanisms in our MoS 2 /TPS photodiode with a positive bias applied. Furthermore, photoresponsivity ( R ), external quantum and efficiency (EQE) are important indicators of the device performance as defined by the following equations R=IphPS$$\begin{eqnarray}R = \frac{{{I}_{{\rm{ph}}}}}{{PS}}\ \end{eqnarray}$$ EQE=Rhceλ$$\begin{eqnarray}{\rm{EQE}} = R\frac{{hc}}{{e\lambda }}\ \end{eqnarray}$$where S is the effective area, e is the electron charge, h is Planck's constant, and c is the speed of light.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…When α = 0, the photocurrent is determined by the photogating effect involving the trapping state; when α = 1, the photocurrent is determined by the photoconductive effect. [ 32,33 ] The extracted α is between 0 and 1, indicating the coexistence of these two mechanisms in our MoS 2 /TPS photodiode with a positive bias applied. Furthermore, photoresponsivity ( R ), external quantum and efficiency (EQE) are important indicators of the device performance as defined by the following equations R=IphPS$$\begin{eqnarray}R = \frac{{{I}_{{\rm{ph}}}}}{{PS}}\ \end{eqnarray}$$ EQE=Rhceλ$$\begin{eqnarray}{\rm{EQE}} = R\frac{{hc}}{{e\lambda }}\ \end{eqnarray}$$where S is the effective area, e is the electron charge, h is Planck's constant, and c is the speed of light.…”
Section: Resultsmentioning
confidence: 83%
“…When 𝛼 = 0, the photocurrent is determined by the photogating effect involving the trapping state; when 𝛼 = 1, the photocurrent is determined by the photoconductive effect. [32,33] The extracted 𝛼 is between 0 and 1, indicating the coexistence of these two mechanisms in our MoS 2 /TPS photodiode with a positive bias applied. Furthermore, photoresponsivity (R), external quantum and efficiency (EQE) are important indicators of the device performance as defined by the following equations…”
Section: Photoresponse Performance Of the Mos 2 /Tps Photodiodementioning
confidence: 76%
See 1 more Smart Citation
“…26 Stacking this BP with TMPS 4 using the interfacial vdW force may further enrich the characteristics of both materials, especially promoting the application in spintronics and thermoelectric. [27][28][29] This is challenging because undesired band shifts will lead to photocarrier complexation and block photocarrier transport. 30,31 The layered dependence and diverse band structure of 2D materials make the structure a possible type II energy band alignment interface without electron and hole barriers, which is important for efficient charge transport and collection.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, most PtS 2 -based heterostructures have been fabricated using dry transfer of mechanically exfoliated flakes. [29][30][31] Although, this method is simple and quick but it possesses limitations for large-scale growth fabrication. So far, only Liang Li et al reported a combination of PtS 2 /MoS 2 heterostructures utilizing the same dry transfer approach, concentrating on visible range detection.…”
Section: Introductionmentioning
confidence: 99%